2007
DOI: 10.1111/j.1570-7458.2006.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trap type, trap colour, and trapping location on the capture of the pine moth, Thaumetopoea pityocampa

Abstract: Studies were conducted to evaluate the effect of type, location, and colour of traps baited with 1 mg of the sex pheromone (Z)‐13‐hexadecen‐11‐ynyl acetate in polyethylene vials on the capture of the pine processionary moth, Thaumetopoea pityocampa (Denis & Schiffermüller) (Lepidoptera: Thaumetopoeidae), males. The experiments were carried out during two flight seasons in 2002 and 2003 at a low elevation Mediterranean pine forest on the hill of Goritsa (Magnesia, Thessaly, Central Greece). The hill is covered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Athanassiou et al . () and Bonsignore and Manti () both observed that trap captures of PPM did not differ between edge and within pine stand locations; however, in both studies, more moths were captured in open, low density stands, suggesting a preference for lighter, sunnier situations. Other studies have generally confirmed this inclination and have revealed that PPM nests are more abundant on trees located at the forest edges, indicating a clear preference for female moths to orientate preferentially to edge trees (Samalens & Rossi, ; Dulaurent et al ., ; Regolini et al ., 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Athanassiou et al . () and Bonsignore and Manti () both observed that trap captures of PPM did not differ between edge and within pine stand locations; however, in both studies, more moths were captured in open, low density stands, suggesting a preference for lighter, sunnier situations. Other studies have generally confirmed this inclination and have revealed that PPM nests are more abundant on trees located at the forest edges, indicating a clear preference for female moths to orientate preferentially to edge trees (Samalens & Rossi, ; Dulaurent et al ., ; Regolini et al ., 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Adult control by mass-trapping and mating-disruption are also adoptable techniques. Different traps and marketed synthetic pheromones vary in their efficiency in capturing males of pine processionary moths (Martin, 2015), and the results can be influenced by various factors, including trap placement, type of trapping, pheromone source and other visual stimuli such as the colour of the trap surface (Athanassiou et al, 2007(Athanassiou et al, , 2017Brockerhoff et al, 2013;Jactel et al, 2006). Very little information is available on the masstrapping of adult pine processionary moths.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained confirmed that an allochronic speciation process of the PPM is ongoing in the Leiria area, in Portugal. PPM range has been subjected to intensive survey through international research networks over its whole range ; the singleness of the SP population is therefore remarkable, even if an early spring emergence concerning a very low percentage of adults was documented in a Greek population (Athanassiou et al, 2007). References addressing the relative importance of allopatric vs. sympatric speciation processes often concede that even in a sympatric context, it is generally difficult to exclude the existence of an initial period of divergence occurring under allopatry (Yukilevich, 2014).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%